Monocentric Growth and Productivity Spillovers in Vietnam : A Spatial Regression Approach - Nguyen, Hai Minh; Tran, Ky Thien (Indian Journal of Finance, 2022)
After more than 30 reforms (1986 – 2018), although Vietnam’s economic growth has had inevitable fluctuations, it remained higher than the regional and world average with an average increase throughout nearly 7%/year. However, if we consider the spatial dimension alone, the growth is not proportional. The productivity growth has been mainly concentrated within the major urban areas and their neighboring provinces. With this evidence, the purpose of this study was to verify whether there existed an extreme productivity growth and a spillover effect in Vietnam by spatial econometric tests to survey data and remote sensing data. The I-Moran test results showed a close relationship between the light density at night, industrial density, enterprise efficiency, and labor quality. Furthermore, the I-Moran test provided evidence that productivity spills existed among several firms. The research results suggested that attracting and expanding production in target areas, infrastructure, and incentives must ensure positive spillovers at levels higher than those obtained from experimental research.